Representatividade adequada e acesso coletivo à justiça: a influência das class actions estadunidenses nas ações coletivas do Brasil - Vescovi, Thaiz da Silva (2010)
The present work searchs to verify if the adequacy of representation of the United States system of class action can be used in the Brazilian legal system to extend the fundamental right of access to justice. The deductive method and the type of exploratory and comparative research were used. In the introduction it was presented problematic, its importance and the division of the work in five chapters. The first chapter one discoursed on the methodology of comparing legal systems and the possibility of comparison between civil law and common law. One presented the origin, the traits and characteristic features of Roman-Germanic system, and the Anglo-Saxon, bringing then the comparison between these systems. The second chapter presented the basic characteristics and evolution of the concept of access to justice at the Brazilian and U.S. governments, both individually and collectively, as pointed out in access to justice as a fundamental human right and fundamental mechanism to protect these rights. It was found that access to justice in a democratic state has significance of social justice and not just only a guarantee of the right of petition, with relevance to the individual and the community even more. It was demonstrated that this concept has no major changes in Brazil and the U.S., despite this fundamental right had a different evolution in both scenarios. Thus, it was also noted that access to justice suffers from problems in its execution, especially on collective standing. The third chapter describes the role of United States class action mechanism to guarantee human, fundamental and social rights. Talked about the concept of this action, the evolution of the class action’s scenario in the U.S., the interests protected by the rules of pertinence, standing and adequacy of representation, opt in and opt out, for analyzing the effectiveness of access to justice in this sense. The fourth chapter made the same analysis of the third chapter to Brazilian’s collective suits addressing the concept, the evolution at the Brazilian scenario, the interests protected and relevancy of these actions. At this point, these work decided to limit the study only to the Brazilian’s Public Civil Action, because these are the collective actions closer to US. class actions studied. About that Brazilian action, stood out as is the legitimacy and representativeness appropriate. Talked about the effectiveness of access to justice in the Brazilian collective suit’s standing, as a guarantor of other fundamental rights. Furthermore, there were problems with the massive use of public legitimacy in Brazil. In the fifth chapter, there was an overview about the differences drawn between Brazilian’s collective action and United State’s class action in regard to standing, analyzing which country can provide a more effective access to justice, based on the previous chapters. It was concluded that in the Brazilian state is the propensity for large-scale use of public standing on collective actions, which ends up being a hindrance to a more effective access to justice and other fundamental rights, as compared to the United States system of adequate representation.